2019
DOI: 10.29252/beat-070206
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Simultaneous Administration of Nimodipine, Progesterone, and Magnesium Sulfate in Patients with Severe Traumatic Brain Injury: A Randomized Controlled Trial

Abstract: Objective: To investigate the safety and efficacy of simultaneous administration of nimodipine, progesterone, magnesium sulfate in patients suffering from severe traumatic brain injury (TBI). Methods: Overall, 90 patients with blunt head trauma who were admitted to the Besat hospital, Hamadan University of Medical Sciences, Iran through the Emergency Department in 2017 to 2018 were randomly assigned to the study or control groups each containing 45 patients. In the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…A total of 1844 abstracts were excluded due to the following reasons: no study on TBI ( n = 785), no RCT ( n = 431), laboratory study ( n = 88), delayed intervention (e.g., study on rehabilitation techniques; n = 300), no original article ( n = 222), other reasons ( n = 18).During the further analysis of the 82 studies left, five studies had to be excluded, as the full-text revealed that the studies did not meet the criteria of RCTs; two more articles had to be excluded as the full-texts were only available in Russian/Chinese; three articles were identified as review articles. Therefore, a total of 72 articles [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 1844 abstracts were excluded due to the following reasons: no study on TBI ( n = 785), no RCT ( n = 431), laboratory study ( n = 88), delayed intervention (e.g., study on rehabilitation techniques; n = 300), no original article ( n = 222), other reasons ( n = 18).During the further analysis of the 82 studies left, five studies had to be excluded, as the full-text revealed that the studies did not meet the criteria of RCTs; two more articles had to be excluded as the full-texts were only available in Russian/Chinese; three articles were identified as review articles. Therefore, a total of 72 articles [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58...…”
Section: Resultsmentioning
confidence: 99%
“…For four studies, no impact factor of the publishing journal was listed [ 16 , 38 , 39 , 40 , 76 , 77 ]. Further, 11 articles were not available through the Web of Science database search at all [ 12 , 15 , 33 , 41 , 51 , 55 , 56 , 66 , 74 , 79 , 81 ]. Details on the studies, including specific interventions, number of patients and outcome measures, are attached as a Supplemental Data File .…”
Section: Resultsmentioning
confidence: 99%
“…It affects certain secondary factors involved in the pathophysiology of TBI by blocking N-methyl-D-aspartate (NMDA) receptors and reducing glutamate release. Other neuroprotective mechanisms of magnesium include increasing brain blood flow, obstructing calcium channels, and inhibiting apoptosis [13]. Furthermore, MgSO 4 has been proven for having antinociception properties, mainly due to its antagonistic effect on NMDA receptors (NMDARs).…”
Section: Introductionmentioning
confidence: 99%